Associations of Clinical and Social Risk Factors With Racial Differences in Premature Cardiovascular Disease. Issue 3 (24th May 2022) - Shah, Nilay S.; Ning, Hongyan; Petito, Lucia C.; Kershaw, Kiarri N.; Bancks, Michael P.; Reis, Jared P.; Rana, Jamal S.; Sidney, Stephen; Jacobs, David R.; Kiefe, Catarina I.; Carnethon, Mercedes R.; Lloyd-Jones, Donald M.; et al.
Abstract : Background: Racial differences in cardiovascular disease (CVD) are likely related to differences in clinical and social factors. The relative contributions of these factors to Black-White differences in premature CVD have not been investigated. Methods: In Black and White adults aged 18 to 30 years at baseline in the CARDIA study (Coronary Artery Risk Development in Young Adults), the associations of clinical, lifestyle, depression, socioeconomic, and neighborhood factors across young adulthood with racial differences in incident premature CVD were evaluated in sex-stratified, multivariable-adjusted Cox proportional hazards models using multiply imputed data assuming missing at random. Percent reduction in the β estimate (log-hazard ratio [HR]) for race quantified the contribution of each factor group to racial differences in incident CVD. Results: Among 2785 Black and 2327 White participants followed for a median 33.9 years (25th–75th percentile, 33.7–34.0), Black (versus White) adults had a higher risk of incident premature CVD (Black women: HR, 2.44 [95% CI, 1.71–3.49], Black men: HR, 1.59 [1.20–2.10] adjusted for age and center). Racial differences were not statistically significant after full adjustment (Black women: HR, 0.91 [0.55–1.52], Black men: HR 1.02 [0.70–1.49]). In women, the largest magnitude percent reduction in the β estimate for race occurred with adjustment for clinical (87%), neighborhood (32%), and socioeconomic (23%) factors. In men, the largest magnitude percent reduction in the β estimate for race occurred with an adjustment for clinical (64%), socioeconomic (50%), and lifestyle (34%) factors. Conclusions: In CARDIA, the significantly higher risk for premature CVD in Black versus White adults was statistically explained by adjustment for antecedent multilevel factors. The largest contributions to racial differences were from clinical and neighborhood factors in women, and clinical and socioeconomic factors in men.